Analysis of co-infection in severe and critical patients with influenza A (H1N1) pneumonia using metagenomic next-generation sequencing on bronchoalveolar lavage samples - Gong, Weitao; Ma, Xiaolin; Wang, Gaoming; Guo, Yongzhong; Zhuo, Zhiyuan; Han, Conghui; Wu, Yanmin (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesThe study aimed to clarify the co-infection patterns in adult patients with severe influenza A (H1N1) pneumonia using Metagenomic Next-Generation Sequencing (mNGS) and to examine their impact on clinical outcomes, particularly focusing on the differences between severe and critical patient groups.MethodsThis retrospective analysis evaluated bronchoalveolar lavage fluid (BALF) from 53 adult patients diagnosed with severe influenza A (H1N1) pneumonia. Patients were categorized into severe and critical groups depending on the need for invasive ventilation. mNGS was utilized to detect and analyze co-infections, which included fungal, bacterial and viral pathogens. Statistical analysis was conducted to assess the prevalence of these co-infections and their association with clinical outcomes, such as 28-day mortality.ResultsIn the cohort, 48 patients (90.6%) experienced co-infections. In the severe group, fungal infections were noted in 14 patients (66.7%), bacterial in 4 patients (19.0%), and viral in 11 patients (52.4%). Among the critical group, 22 patients (68.8%) had fungal, 23 patients (71.9%) had bacterial, and 10 patients (31.3%) had viral co-infections. There was a significantly higher incidence of co-infections in critical patients (P = 0.0002), with notable differences in Acinetobacter baumannii prevalence between the groups (P = 0.0339). Aspergillus emerged as the predominant fungal genus across the study. Septic shock (odds ratio [OR] 33.63[4.29−538.3]; P = 0.003) and fungal co-infection (OR 24.42[1.98−810.6]; P = 0.029) were identified as independent risk factors for 28-day mortality.ConclusionThe study revealed a high rate of co-infections in both severe and critical patients suffering from influenza A (H1N1) pneumonia, with a higher frequency of bacterial infections in critical patients. Importantly, septic shock and fungal co-infections were independently associated with increased 28-day mortality, highlighting the need for monitoring and management of co-infections in these patients.